Fiber optic Fabry-Perot interferometer sensor: an efficient and fast approach for ammonia gas sensing - Kanawade, Rajesh; Kumar, Ajay; Pawar, Dnyandeo; Late, Dattatray; Mondal, Samir; Sinha, Ravindra K. (Journal of the Optical Society of America B-Optical Physics, 2019)
In this work, we propose and demonstrate a Fabry-Perot-interferometer-based polydimethylsiloxane (PDMS) and poly(methyl methacrylate) (PMMA)-composite-coated optical sensor for ammonia and volatile organic compounds (VOCs) detection at room temperature. The principle of sensing is based on change in the cavity length of the FP cavity in the presence of varied concentrations of gases, which results in changes in the total reflectance due to the shift in wavelength of an interference pattern. The sensing composite material was coated on a single-mode optical fiber by using a simple dip-coating technique and explored it for sensing. The ammonia and VOCs measurements were performed for concentrations ranging from 5 to 500 ppm. The corresponding sensitivity and limit of detection of the developed sensor for ammonia gas detection was observed of the order of around 4.16 pm/ppm and 4.8 ppm, respectively. The response and recovery times of the sensor were found to be of the order of 50 s and 10 s, respectively, for the ammonia gas. This sensor provides a simple, cost-effective, highly sensitive, and repeatable approach to measure ammonia gas and other VOCs at room temperature and could fulfill the demands of industrial applications. (C) 2019 Optical Society of America

Negative axicon tip-based fiber optic interferometer cavity sensor for volatile gas sensing - Kanavvade, Rajesh; Kumar, Ajay; Pawar, Dnyandeo; Vairagi, Kaushal; Late, Dattatray; Sarkar, Sudipta; Sinha, Ravindra K.; Mondal, Samir (Optics Express, 2019)
In this research work we demonstrated negative axicon optical fiber tip filled with Polydimethylsiloxane (PDMS) as a sensor platform for volatile organic gases detection at room temperature. The response of the sensor was measured with various Volatile Organic Compounds (VOCs) such as Chloroform, Hexane, Isopropanol, Acetone, Toluene and Methanol in the concentration ranging from 5 to 200 ppm. The corresponding sensitivity and limit of detection (LOD) of the developed sensor for the measured VOCs were observed between the order of around 23.7 to 3.2 pm/ppm and 0.84 to 6.10 ppm, respectively. The response and recovery time of sensor were found between the order of 30 to 57 seconds and 8 to 25 seconds respectively for the measured VOCs. Thermal stability of the developed sensor was also studied at 30-70 degrees C with intervals of 10 degrees C. The principle of sensing is based on change in the length of the Fabry-Perot Interferometric (FPI) cavity in the presence of varied concentrations of VOCs, which results in changes in the shift in wavelength of an interference pattern attributed to the change in PDMS filling the cavity length (swelling). The experimentally observed trends in the relative swelling of PDMS with VOCs are found in agreement with the theoretically calculated values obtained from the Hansen solubility parameter (HSP). The developed gas sensor has the potential to fulfill the demands of industrial applications.